2023
DOI: 10.3390/genes14051093
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Non-Coding RNA and mRNA Profiles Reveals the Mechanisms of Rumen Development Induced by Different Types of Diet in Calves

Abstract: Selecting suitable feed types and understanding the gastrointestinal digestive mechanism are helpful for the growth and health of calves in intensive dairy farming. However, the effects on rumen development of changing the molecular genetic basis and the regulatory mechanism by using different feed types are still unclear. Nine 7-day-old Holstein bull calves were randomly divided into GF (concentrate), GFF (alfalfa: oat grass = 3:2) and TMR (concentrate: alfalfa grass: oat grass: water = 0.30:0.12:0.08:0.50) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The study further demonstrated that feeding only concentrated feed to calves could cause a series of inflammatory reactions, lead to immune system disorders, and affect the normal growth and development of the rumen, but there were certain differences from previous research results at the genetic level [93]. Although the study found reliable results in rumen microorganisms body metabolism, due to the small number of test samples and the lack of relevant data on rumen microbial metabolism, further research will be needed in the individual growth, rumen development and disease of calves.…”
Section: Discussionmentioning
confidence: 60%
“…The study further demonstrated that feeding only concentrated feed to calves could cause a series of inflammatory reactions, lead to immune system disorders, and affect the normal growth and development of the rumen, but there were certain differences from previous research results at the genetic level [93]. Although the study found reliable results in rumen microorganisms body metabolism, due to the small number of test samples and the lack of relevant data on rumen microbial metabolism, further research will be needed in the individual growth, rumen development and disease of calves.…”
Section: Discussionmentioning
confidence: 60%
“…RNA-seq-based host transcriptome analysis has been extensively studied in ruminants to understand changes in rumen tissue with age, types of diet, weaning, and metabolic disorders at the molecular level [19,[85][86][87]. The rumen separates the individual ruminant from the microbiome, but also interacts with the microbiome, thereby affecting the immune status and physiology of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analyses suggested that transforming growth factor-β might be another hormone mediating the growth of rumen epithelium from pre-weaned to post-weaned calves [131]. Similarly, integrated analysis of differentially expressed long non-coding RNAs and mRNAs revealed thyroid hormone as another candidate hormone that mediates rumen development in postnatal animals [132,133].…”
Section: Hormonesmentioning
confidence: 99%